Evaluasi Penerapan Metode Cell Splitting Terhadap Peningkatan Kapasitas dan Kualitas Jaringan LTE - Hasanah Putri; Febryyanti Nawang Wulan; Fiqhi Anugerah; Ainur Rizqi Aulia; Dhea Anjar Sari (Jurnal Rekayasa Elektrika, 2019)
Based on the results of the survey and drive test on Jalan Karawitan Bandung - Indonesia, the value of radio parameters is considered poorly accepted by the Standard Operator Performance Indicator (KPI) standards. The parameters observed were Reference Received Power (RSRP) -90 dBm, Signal to Interference Noise Ratio (SINR) 5 dB, and throughput 800 Mbps. This region is a potential market region including tourist attractions, businesses, offices, and housing. In addition, based on data from the Operating Support System (OSS), there is an imbalance between traffic users and cell capacity that supports network quality. In addition, there are customer complaints about the quality of the Long Term Evolution (LTE) network in the office area. In this article cellseparation planning is carried out to increase the capacity and quality of LTE networks using Atoll 3.3 software. The results of planning show that an increase in network performance is the value of RSRP increased by 13.32%, SINR increased by 52.75%, and throughput increased by 236%.